Indicadores de desempenho em um departamento jurídico: um roteiro direcionador para sua construção - Flach Junior, Pedro (Universidade do Vale do Rio dos Sinos, 2015)
The intricate corporate environment requires that distinct areas of knowledge be aligned with the focus of a specific business. The School of Business Administration enables the executive to define objective guidelines for measuring business performance. Differently, the Law School assists the executive with the management of the demands regarding the various divisions of the corporate structure. The relation between objective methods of management and the existing subjective aspects which the administration of a legal department entails, is one of the challenges to be tackled by the professionals controlling its structuring and managing. The role of the legal manager is to structure and control a legal department responsible for conducting the legal demands of a business, and it must take into consideration the same managerial principles applicable to the administration of other business divisions, with a focus on the key performance indicators. Once being inserted into the structure of a company whose performance is entitled to constant monitoring, the legal department is also subject to having the control of its performance, being this the role of the legal manager. The creation and usage of specific indicators for the legal department performance measurement is the challenge that must be observed by the modern legal manager. Using the Design Research methodology, the present study aims to provide a guiding framework to help the legal department executive define the managing strategies for the department, identify the key elements and therefore, formulate effectual Key Performance Indicators - KPIs, since they are directly related to the business and aligned with the specific reality of a determined business.
Keywords: Medição de performance; Key performance indicators; Gestão; Departamentos jurídicos; Measuring performance; Management; Legal departments; ACCNPQ::Ciências Sociais Aplicadas::Administração